Indonesian Automatic Speech Recognition For Command Speech Controller Multimedia Player - Wardhany, Vivien Arief; Sukaridhoto, Sritrusta; Sudarsono, Amang (Politeknik Elektronika Negeri Surabaya (PENS), 2014)
The purpose of multimedia devices development is controlling through voice. Nowdays voice that can be recognized only in English. To overcome the issue, then recognition using Indonesian language model and accousticc model and dictionary. Automatic Speech Recognizier is build using engine CMU Sphinx with modified english language to Indonesian Language database and XBMC used as the multimedia player. The experiment is using 10 volunteers testing items based on 7 commands. The volunteers is classifiedd by the genders, 5 Male & 5 female. 10 samples is taken in each command, continue with each volunteer perform 10 testing command. Each volunteer also have to try all 7 command that already provided. Based on percentage clarification table, the word âKananâ had the most recognize with percentage 83% while âpilihâ is the lowest one. The word which had the most wrong clarification is âkembaliâ with percentagee 67%, while the word âkananâ is the lowest one. From the result of Recognition Rate by male there are several command such as âKembaliâ, âUtamaâ, âAtas â and âBawahâ has the low Recognition Rate. Especially for âkembaliâ cannot be recognized as the command in the female voices but in male voice that command has 4% of RR this is because the command doesnât have similar word in english near to âkembaliâ so the system unrecognize the command. Also for the command âPilihâ using the female voice has 80% of RR but for the male voice has only 4% of RR. This problem is mostly because of the different voice characteristic between adult male and female which male has lower voice frequencies (from 85 to 180 Hz) than woman (165 to 255 Hz).The result of the experiment showed that each man had different number of recognition rate caused by the difference tone, pronunciation, and speed of speech. For further work needs to be done in order to improving the accouracy of the Indonesian Automatic Speech Recognition system.Keywords: Automatic Speech Recognizer, Indonesian Acoustic Model, CMU Sphinx, indonesian Language Model, Recognition Rate, XBMC.